Design of Horizontal Mixer Capacity of 15 Kilograms - Achmad Tohasan; Muhamad Yusup Ependi; Andri Hermawan (Fakultas Teknik Universitas 17 Agustus 1945 Cirebon, 2021)
Some home industries, such as the bakery industry, in their production still use manual methods or human labor to mix the bread dough until it is smooth. The disadvantages of using the manual method are that production takes a long time, requires a lot of energy, requires more than one person to mix all the ingredients for the bread dough. So research is needed on the design of a tool that can facilitate the production of bread, namely a mixer. The purpose of this study is to design a horizontal mixer machine and to design a horizontal dough mixer machine with a capacity of 15. This research is supported by literature studies in the form of books and internet sites. The design of a bread dough mixer machine with a capacity of 15 kg which describes in detail the machine elements used includes calculating the power of the driving motor, the diameter of the pulleys, the diameter and number of teeth on the gears, as well as determining the shaft material and shaft diameter used, the type of belt, and the dough mixing lever. This designed mixing machine has a capacity of 60 kg/hour which is capable of producing 1500 pieces of bread in 1 hour, while the components used consist of 1 motor with a power of 1.5 kW, 2 pulleys, 2 continuous rotation shafts, 1 rotating shaft. turning the mixing spoon, 2 belts, 2 gears, and 4 bearings that support the shaft. The bread dough reservoir is made of stainless plates to avoid rust which is able to maintain cleanliness and sterilize food dough, the shaft material uses ST 60 carbon steel. It is hoped that using a horizontal mixer machine as a result of this design can be one of the solutions in fulfilling production capacity both in quality as well as production quantity.